An Approach to the Educational Relationships Mediated by the Thecnologies at the School Juan Manuel Gonzalez (Colombia) (2020)
The text gathers the approach and outcomes of the research carried out in the I.E Juan Manuel Gonzalez in Colombia, town of Dosquebradas Risaralda. The main aim of this research is to identify the educational relations mediated by ICT in the classroom. It characterizes through the use of surveys, new ways of communicative interaction, linked to an increasingly powerful technological basis that identifies the sophistication of cognitive capitalism, in its attempt to highlight the importance of the inherent axiological challenge to educational work, in order to create a space for collective reflection that strengthens a broader horizon of comprehension about the educational issue